Multiple Urethral Hemangiomas Associated with Urethral Stricture: An Uncommon Aetiology for Urethral Bleeding - Raquel Varea-Malo; Félix Campos-Juanatey; José Antonio Portillo Martín; Luisana Castillo Carvajal (Case Reports in Urology)
Urethral haemangiomas are rare benign vascular tumours. They usually cause painless urethral bleeding and haematospermia. Urethroscopy is the preferred diagnostic tool, while complementary radiologic studies could describe the extension of the tumour. Treatment should be tailored to each case, considering size, location, and number of lesions. We present a case of a male patient diagnosed with urethral haemangiomas following painless spontaneous urethral bleeding associated with voiding symptoms.